(untitled) (International Association of Biologicals and Computational Digest, 2022)
Floristic studies help us to assess the plant wealth and its potentiality of any given area. Floristic studies also help us to understand the basic aspects of biology such as speciation, isolation, endemism and evolution. Flora of any area is not fixed up. It changes from time to time. Various ecological factors, mostly biotic, change the floristic components. The total number of species may be changed; dominant species may be replaced with other species; the floristic composition, i.e., family: genus: species ratio may be changed. Umargam taluka is selected for the floristic studies. Whole area is rich in plant diversity. Floristic study of Convolvulaceae family in Umargam taluka, Valsad district, Gujarat, India, was carried out. A total of 23species under 8 genera belonging to the family Convolvulaceae were collected and identified. For each species botanical name, local name, habitat, flowering time, distribution and Taxonomic description have been mentioned.